Anthroponyms in the Kazakh and Turkish languages - Mnaidarova, Miramgul (Razprave in gradivo - Inštitut za narodnostna vprašanja (1990), 2025)
This study examines the origin and historical development of anthroponyms in the Kazakh and Turkish languages. Drawing on 21 academic sources, including books, peer-reviewed articles, and conference papers, it aims to detect similarities and differences in the evolution of anthroponyms and their use in contemporary linguistic contexts. The analysis revealed a lack of specific studies on the morphological structure of anthroponyms in both Kazakh and Turkish. The study confirmed the significance of general onomastics and anthroponymy in understanding the morphological structure of anthroponyms in these languages and highlighted ongoing disagreements on the role of the Turkic linguistic basis in their emergence and development. The obtained results can be used in the teaching of Kazakh and Turkish in academic settings and can also support efforts to preserve cultural heritage.
Keywords: etimologija; etymology; grammar; history; onomastics; onomastika; slovnica; structure; struktura; zgodovina